Internal carotid artery ectasia: A case report of incidental diagnosis after post-traumatic headache - Sami F. Almalki, MBBS; Abdulelah S. Almousa; Abdullah K. Alarfaj, MBBS; Shaden S. AlMousa, MBBS (Radiology Case Reports, 2024)
Internal carotid artery ectasia (ICAE) is a rare vascular abnormality characterized by dilation and tortuosity of the internal carotid artery (ICA) beyond normal limits. ICAE is typically asymptomatic but can manifest with symptoms such as headache and dizziness. The exact cause of ICAE remains uncertain, but both congenital and acquired factors, including trauma, have been implicated. A 35-year-old female presented to the Emergency Room with severe headache and dizziness following a traumatic injury. Neurological examination revealed no deficits. Computed tomography (CT) scan showed an elongated and prominent right supraclinoid internal carotid artery with mural wall calcification. Subsequent magnetic resonance imaging (MRI) confirmed the diagnosis of internal carotid artery ectasia (ICAE) without significant stenosis or malformation. The patient remained asymptomatic during follow-up visits. Proactive monitoring was advised to detect potential complications at an early stage. This case emphasizes the incidental detection of ICAE in a patient with post-traumatic headache. ICAE is a rare condition with an elusive etiology, and its management depends on factors such as symptom severity and associated risks. Conservative management is often recommended for asymptomatic cases.